Enhance Control Mobile Compiuting Improvement in Quality Data Acquisition in Simulation - Efendi, Syahril; Aryza, Solly; Mardiansyah, Heru; Ahmadi, Fauzan Nur; Khowarizmi, Al- (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research is a research and development (R&D) process with software design and testing using the v-model software development life cycle (SDLC) method, consisting of stages: (1) requirements modeling, (2) architectural design, (3) component design, (4) code generation, (5) unit testing, (6) integration testing, (7) system testing, (8) acceptance testing. Unit testing method using a white-box technique with base-path test, flowgraph, independent path on "DigiChip" software. Testing integration, system, acceptance with black-box techniques. The functional suitability aspect was tested with a feature run test questionnaire and a test case. The maintainability aspect is tested by measuring maintainability index (MI), duplication source code, line of code (LoC), cyclomatic complexity (CC). The portability aspect is tested by installing on various hardware configurations, various versions of the Android OS kernel. The material and media test used a material expert and media expert questionnaire. The usability aspect was tested using the USE Questionnaire and the calculation of Cronbach's Alpha through SPSS. This paper describes the main advantages of this DAS module which is that it can be manufactured at a very affordable price and provides good performance as is commonly used in industrial control systems. In motor control systems, alternative data acquisition system (DAS) modules can use the LabVIEW interface. The DAS module is controlled by the ATmega64 AVR micro controller which will communicate in both directions with LabVIEW using the serial communication method. Which is used to obtain 8-bit digital input, 8-bit digital output, 8 analog input channels, and also 2 analog output channels. Digital inputs can be used for 0-5V and 0-24V voltages. The digital output is made open collector with a "low" voltage of 0.276V. For analog inputs and analog outputs, this system has an average error of 14.47mV for the input range of 1-5V; 72.34mV for the 0-10V input range; 0.037mA for 4-20mA input range, and 16.2mV for 0-10V output range. This system is not designed for use in applications that require real-time accuracy and fast accuracy.